Risk of firearm injuries among children and youth of immigrant families - Saunders, Natasha R. (CMAJ, 2017)
BACKGROUND: Firearm injuries contribute to substantial morbidity and mortality. The immigrant paradox suggests that, despite being more socially disadvantaged, immigrants are less likely than nonimmigrants to have poor outcomes. We tested the association of immigrant characteristics with firearm injuries among children and youth. METHODS: We conducted a population-based cohort study involving residents of Ontario aged 24 years and younger from 2008–2012 using health and administrative databases. We estimated rate ratios of unintentional and assault-related firearm injuries by immigrant status using Poisson regression models with Generalized Estimating Equations. RESULTS: We included 15 866 954 nonimmigrant and 4 551 291 immigrant person-years in our analysis. Nonimmigrant males had 1032 unintentional (12.4 per 100 000, 95% confidence interval [CI] 11.7–13.2) and 304 assault-related (3.6 per 100 000, 95% CI 3.2–4.0) firearm injuries. Immigrant males had 148 unintentional (7.2 per 100 000, 95% CI 6.1–8.5) and 113 assault-related (5.5 per 100 000, 95% CI 4.5–6.6) firearm injuries. Compared with nonimmigrants, immigrants had a lower rate of unintentional firearm injury (adjusted rate ratio 0.5, 95% CI 0.4–0.6) but a similar rate of assault-related firearm injury. Among immigrants, refugees had a 43% higher risk of assault-related firearm injury compared with nonrefugees (adjusted rate ratio 1.4, 95% CI 1.0–2.0). Immigrants from Central America and Africa accounted for 68% of immigrants with assault-related firearm injuries. INTERPRETATION: Compared with nonimmigrants, immigrant children and youth had a lower risk of unintentional firearm injury, although the risk of assault-related firearm injury was higher among refugees and immigrants from Central America and Africa. The results suggest that prevention strategies for firearm safety should target nonimmigrant youth as well as these newly identified high-risk immigrant populations.